Investigation of transmission of vaccine strains of African horse sickness virus in weanling foals kept under field conditions following the use of a commercial attenuated live virus vaccine - Guthrie, Alan John (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.